HXE 108 - Approaches to English Literature - November 2005 - PPIK, Pusat Pengajian Ilmu Kemanusiaan (2005)
UNIVERSITI SAINS MALAYSIA First Semester Examination Academic 'Session 2005/2006 November 2005 HXE 108 - Approaches to English Literature Duration: 3 hours